2007
DOI: 10.21914/anziamj.v48i0.86
|View full text |Cite
|
Sign up to set email alerts
|

A simple spatial model for self-heating compost piles

Abstract: We model the increase in temperature in compost piles due to micro-organisms undergoing exothermic reactions. The model incorporates two types of heat release: one due to biological activity; and the other due to the oxidation of cellulosic materials. In this study we also include the consumption of oxygen. We investigate the bifurcation behaviour and compare the results obtained from models that include and exclude oxygen consumption in both one-and two-dimensional geometries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 10 publications
(9 reference statements)
0
33
0
Order By: Relevance
“…The parameter values are based on those previously used by Sidhu et al [15] and are provided in the nomenclature, Table 4. However, before comparing the results obtained from both methods, the accuracy of the numerical solutions need to be established.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The parameter values are based on those previously used by Sidhu et al [15] and are provided in the nomenclature, Table 4. However, before comparing the results obtained from both methods, the accuracy of the numerical solutions need to be established.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…We believe that the effects of temperature gradients and the depletion of cellulosic materials and biomass are negligible for large compost piles for the range of temperatures considered in this study. Moraga et al [11] showed explicitly, from their experimental data of a sewage sludge pile, that the model and parameter values used by Sidhu et al [15] (that is, without air flow) provided reasonable predictions of temperature increases within the pile. Since the present model extends the work of Sidhu et al [15] by including air flow, we believe that the current investigation illustrates the trends when the flow of air is included.…”
Section: Governing Equationsmentioning
confidence: 98%
See 2 more Smart Citations
“…The self-heating model represented well the generic behaviors during composting and the dependence of the phenomena on the kinetic parameters. Sidhu et al (2007) proposed a spatial mathematical model, which consists of equations of conservation of heat and oxygen to estimate the concentration of oxygen and temperature during diffusive-heating composting. Luangwilai et al (2010) also employed a one-dimensional model to describe composting in a convective system by using equations of conservation of heat and oxygen.…”
Section: Introductionmentioning
confidence: 99%